Capabilities of Satellite-Based Precipitation to Estimate the Spatiotemporal Variation of Flood/Drought Class in Poyang Lake Basin - Xianghu Li; Qi Zhang; Xuchun Ye (Advances in Meteorology)
Poyang Lake basin is one of the most frequently affected areas by a variety of flood or drought events in China. Satellite-based precipitation data have greatly improved their temporal and spatial resolution in recent years, but the short length of records limited their applications in some fields. This paper compared and evaluated the creditability of using a short period data series to estimate the statistics characteristics of long period data series and investigated the usefulness of TRMM rainfall data for monitoring the temporal and spatial distribution of flood/drought classes by the Z index method in Poyang Lake basin. The results show that (1) the 1998–2010 data series are sufficiently robust to depict the statistics characteristics of long period data; (2) the intra-annual distribution and interannual variability of flood/drought classes based on TRMM rainfall data matched well with the results from rain gauges data; (3) the spatial agreement between TRMM and interpolated gauges rainfall varied with the precipitation characteristics; and (4) TRMM rainfall data described the similar spatial pattern of flood/drought classes with the interpolated gauges rainfall. In conclusion, it is suitable and credible for flood/drought classes evaluation based on the TRMM rainfall data in Poyang Lake basin.